Investigasi Tingkat Kerawanan Gedung Dalam Rangka Implementasi Mitigasi Gempa Bumi di Fakultas Teknik Universitas Mataram - Teti Zubaidah; Rosmaliati Rosmaliati; Cipta Ramadhani; Dwi Ratnasari; Made Sutha Yadnya; Bulkis Kanata; Paniran Paniran; Abdullah Zainuddin; Kenya Damayanti Priyatna (Universitas Mataram, 2021)
After the 2018 Lombok Earthquake, buildings at the Faculty of Engineering, University of Mataram (FT Unram) were severely damaged and there was no comprehensive treatment. Facilities for earthquake mitigation are still minimal and if available they are not designed and placed properly. Some parts of the building have been renovated but appear unfinished, while there were new constructions that have not been investigated regarding their suitability with earthquake mitigation. Anticipating re-occurrence of a major earthquake in Lombok, it is very necessary to implement earthquake mitigation at FT Unram. In this paper, results of vulnerability investigation of each building will be presented including number, type, and level of damages as well as their locations and detailed documentation of each point of damages in form of pictures and photos/videos. Through this activity vulnerabilities of each building can be identified comprehensively, so that appropriate treatments can be carried out, and the safest evacuation route can be planned as well.